(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The economic development has allowed to many countries of the world a significant advance in the levels of well-being of its population but also it is possible to find new and important problems associated with such a process. Inside them it is necessary to indicate the presence of persistent organic pollutants (POPs), wide group of chemical substances fruit of the human activity which concern the environment and cause important health problems in persons and animals.They are especially harmful due to the fact that they accumulate in live organisms during long time, are transmitted to the future generations and penetrate borders, moving to big distances being distributed and entering in the whole planet. I thas given place to a global and urgent response to reduce and eliminate its liberation in the environment: The Stockholm Convention, which came into force on May 17,2004 (in our country on August 26, 2004). The existence of the POPs constitutes aglobal problem that demands the coordinated action worldwide.